2017
DOI: 10.3389/fpls.2017.01479
|View full text |Cite
|
Sign up to set email alerts
|

PEG Induces High Expression of the Cell Cycle Checkpoint Gene WEE1 in Embryogenic Callus of Medicago truncatula: Potential Link between Cell Cycle Checkpoint Regulation and Osmotic Stress

Abstract: Polyethylene glycol (PEG) can be used to mimic osmotic stress in plant tissue cultures to study mechanisms of tolerance. The aim of this experiment was to investigate the effects of PEG (M.W. 6000) on embryogenic callus of Medicago truncatula. Leaf explants were cultured on MS medium with 2 mg L-1 NAA and 0.5 mg L-1 BAP for 5 months. Then, calli were transferred to the same medium further supplemented with 10% (w/v) 6000 PEG for 6 months in order to study physiological and putative molecular markers of water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 77 publications
(114 reference statements)
3
23
0
1
Order By: Relevance
“…Nonetheless, most studies using both methods agree on a high level of equivalency among them [ 29 , 30 , 31 ]. When considering the different type of material used, a recent study showed the occurrence of similar mitotic indexes and gene expression profiles in M. truncatula leaves grown in a greenhouse and calli-cultured in vitro [ 32 ]. Likewise, our work using M. truncatula overexpressing the MtTdp2α gene revealed a high degree of similarity in the expression pattern of several DNA repair genes in both plants grown in vitro and cell suspension cultures [ 10 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, most studies using both methods agree on a high level of equivalency among them [ 29 , 30 , 31 ]. When considering the different type of material used, a recent study showed the occurrence of similar mitotic indexes and gene expression profiles in M. truncatula leaves grown in a greenhouse and calli-cultured in vitro [ 32 ]. Likewise, our work using M. truncatula overexpressing the MtTdp2α gene revealed a high degree of similarity in the expression pattern of several DNA repair genes in both plants grown in vitro and cell suspension cultures [ 10 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the higher ploidy of M. glaucescens and M. paucispinus cortex cells can be related to the presence of aquifer parenchyma, which is formed by large cells with elevated ploidy and capacity for storing large volumes of water ( De Rocher et al, 1990 ). Indeed, endoreduplication has been associated with adaptation to saline and water stress conditions, extremely dry conditions and elevated temperatures ( Lema-Rumińska, 2011 ; Elmaghrabi et al, 2013 ; Scholes and Paige, 2015 ; Elmaghrabi et al, 2017 ; Elmaghrabi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The different mechanisms are evident as exemplified by the different patterns of expression of several genes with known functions in DNA damage response between the two systems. However, it cannot be ruled out that some of these divergences might be due to the use of different systems (calli vs. plants) or genomic variability; though, a recent study showed the occurrence of similar gene expression profiles in in vitro grown calli and M. truncatula plantlets [ 47 ]. Hence, the presented results are indicative of the use of hTdp1 inhibitor as a tool for future studies aiming to decipher the peculiar roles of the plant Tdp1 genes.…”
Section: Discussionmentioning
confidence: 99%